Anti-metastatic effects of 1, 2, 3, 4, 6-Penta-O-galloyl-β-D-glucose in colorectal cancer: Regulation of cathepsin B-mediated extracellular matrix dynamics and epithelial-to-mesenchymal transition. (October 2022) - Yang, Huihai; Yue, Grace Gar-Lee; Leung, Ping-Chung; Wong, Chun-Kwok; Zhang, Ying-Jun; Lau, Clara Bik-San
Abstract: Despite significant advances in the diagnosis and treatment of colorectal cancer (CRC), metastatic colorectal cancer still poses serious threat to CRC patients. The natural gallotannin 1, 2, 3, 4, 6-penta- O -galloyl-β-D -glucose (PGG) has been shown to possess anti-tumor effects on colon cancer cells, but its anti-metastatic effect is yet to be investigated. In this study, the effects of PGG on cell proliferation, colony formation ability, motility, migration were investigated in colon cancer cells using BrdU, colony formation, scratch, and transwell assays, respectively. Western blot assay was used for assessing protein expression. The orthotopic colon tumor-bearing mouse model and human colon cancer metastatic mouse model were employed to evaluate the anti-metastatic effects of PGG. Results showed that PGG exhibited not only anti-proliferative and colony formation inhibitory effects, but also inhibition on cell adhesion, motility, and migration in both HCT116 and colon 26-M01 cells via modulating protein expression of cathepsin B, FAK, cofilin, and epithelial-to-mesenchymal transition related proteins. In addition, PGG (10 or 15 mg/kg, i.p .) could significantly inhibit liver and lung metastasis in colon cancer metastatic mice models. Furthermore, PGG could regulate the populations of T cells, macrophages, and MDSCs, while the levels of IL-2, IL-6, IL-10, IFN-γ, and TNF-α were altered after PGG treatment in metastatic CRC mice. This is the first report of the anti-metastatic effects of PGG by regulating cathepsin B-mediated extracellular matrix dynamics and epithelial-to-mesenchymal transition process in CRC. Our findings suggested that PGG has great potential to be developed as an anti-metastatic agent for metastatic CRC. Graphical Abstract: ga1 Highlights: In the present study, the in vitro and in vivo anti-metastatic effects of PGG were firstly reported. PGG could decrease cathepsin B-mediated ECM dynamics and modulate multiple proteins that are activated by ECM remodeling. PGG could modulate EMT process via regulating proteins such as β-catenin, snail, MMP2, MMP9, N-cadherin, and E-cadherin. The promising preclinical results support further drug development of PGG as an anti-metastatic agent in CRC therapy.